IMPLEMENTASI METODE DRILL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS III PADA MATA PELAJARAN BAHASA INDONESIA DI MI MIFTAHUL ULUM PACAR PELUK - Humairoh, Zuni; Kahimah, Luthfiyatul (Prodi PGMI Institut Agama Islam Bani Fattah Jombang, 2023)
Drill is a way of teaching by providing exercises on what students have learned so that they acquire a certain skill. With this in mind, this research is focused on (1) How to implement the Drill method in learning Indonesian for class III at Madrasah Ibtidaiyah Miftahul Ulum (2) How is the effectiveness of learning the drill method in Indonesian class III subjects at Madrasah Ibtidaiyah Miftahul Ulum (3) How improvement of students' reading ability after applying the drill method in class III Indonesian subjects at Madrasah Ibtidaiyah Miftahul Ulum. This type of research is a case study with a case study research approach. Data collection techniques using interviews, observation and documentation. The data analysis technique uses an analysis of checking the validity of the data by extending observations, increasing persistence in research. The results of the study show (1) the application of reading Indonesian using the drill method by students, can be classified into several stages, namely: (a) the opening stage, saying greetings and students answering together then reading hadhoroh, Al-fatihah and a series of short letters (b) core learning, conducting learning (c) closing learning carried out by all students. Then the teacher takes a position in front facing all students to lead the prayer as usual the teacher gives the signal. The results of the study indicate that the drill method can improve students' reading skills, it can be seen that the average value of learning outcomes has increased. The data obtained from participants who completed learning reached 17 students and those who did not completed as many as 10 students with a success percentage of 50%, indicating that there is a improvement of learning outcomes of students who completed reached 18 students and who did not complete as many as 9 students with a percentage of 60%., students who completed learning reached 21 students and those who had not completed as many as 6 students.